Optimal Multiple Sink Nodes Deployment in Wireless Sensor Networks Based on Gene Expression Programming - Shucheng Dai; Changjie Tang; Shaojie Qiao; Kaikuo Xu; Hongjun Li; Jun Zhu (2010 Second International Conference on Communication Software and Networks, 2010)
In wireless sensor networks (WSN) data transmission is usually performed by sensors in manner of multi-hop forwarding towards a central static control center (sink). A lot of cheap, low-powered and energy-limited sensors are deployed in the monitored area and some of these nodes closer to the sink node use up their energy more quickly than other nodes because they relay more packets. Although most of the sensor nodes have enough energy left to work, the energy consumption imbalance leads to connectivity holes and coverage holes, and finally the whole network failure. The main contributions of this paper include: (a) a new scheme based on multiple sink nodes is proposed to prolong the network lifetime and to reduce the response time. It is effective, especially in the target tracking applications, (b) the deployment strategy with given number of multiple sink nodes is explored in the grid sensor network, (c) Gene Expression Programming based Multiple Sink Nodes deployment algorithm (GEP-MSN) is proposed to optimally deploy multiple sink nodes over the monitored region, (d) a data transmission cost model (TCM) is introduced to measure the cost for optimizing during the transmission phase, (e) extensive simulations are conducted to show that the scheme can greatly extend the network lifetime by around 16.6% and 36.3% on average compared with two naive methods based on random distributed sink nodes.